Quantifying Dispositional Fear as Threat Sensitivity: Development and Initial Validation of a Model-Based Scale Measure. (April 2020) - Kramer, Mark D.; Patrick, Christopher J.; Hettema, John M.; Moore, Ashlee A.; Sawyers, Chelsea K.; Yancey, James R.
The Research Domain Criteria initiative aims to reorient the focus of psychopathology research toward biobehavioral constructs that cut across different modalities of measurement, including self-report and neurophysiology. Constructs within the Research Domain Criteria framework are intentionally transdiagnostic, with the construct of "acute threat, " for example, broadly relevant to clinical problems and associated traits involving fearfulness and stress reactivity. A potentially valuable referent for research on the construct of acute threat is a structural model of fear/fearlessness questionnaires known to predict variations in physiological threat reactivity as indexed by startle potentiation. The aim of the current work was to develop an efficient, item-based scale measure of the general factor of this structural model for use in studies of dispositional threat sensitivity and its relationship to psychopathology. A self-report scale consisting of 44 items from a conceptually relevant, nonproprietary questionnaire was first developed in a sample of 1, 307 student participants, using the general factor of the fear/fearlessness model as a direct referent. This new Trait Fear scale was then evaluated for convergent and discriminant validity with measures of personality and psychopathology in a separate sample ( n = 213) consisting of community adults and undergraduate students. The strong performance of the scale in this criterion-validation sample suggests that it can provide an effective means for indexing variations along a dispositional continuum of fearfulness reflecting variations in sensitivity to acute threat.